Dreaming Big (Symphony in the Flint Hills, 2016)
Ask Flint Hills ranchers about their secret to success and they’ll tell you that they don’t raise cattle, they raise grass.
Keywords: grass; fertilizer; shallow soils; diverse; plant/animal life; nature conservancy; barns; SEA WALL; Dave Leiker